Proteção social e famílismo: um estudo sobre as percepções relativas ao empobrecimento feminino a partir dos Programas de Transferências de Renda na Política de Assistência Social no Município de Cascavel- PR - Gomes, Pedro Ernane (2023)
This study looked at Social Protection and Familism and their perceptions of Female Impoverishment based on Income Transfer Programs in the Social Assistance Policy, carried out with single-parent female and two-parent families, as well as with the Coordinators, executors of this policy in the Municipality of Cascavel-PR. The aim was to understand the relationship between the familism that characterizes the Social Assistance Policy and social assistance programs and the impoverishment of the female population, with reference to income transfer programs, based on the burden that these programs impose on women, whether they are the head of the family or not. This study was based on the following guiding question: To what extent does the familism that characterizes the Social Assistance Policy and social assistance actions focused on cash transfers contribute to or reinforce the condition of women in poverty from the perspective of the families served by the CRAS and the Coordinators of these services? In methodological terms, this was a qualitative and quantitative exploratory study. It used a literature review, documentary research, a questionnaire and interviews. The data was analyzed using the content analysis technique, which made it possible to problematize the meaning and functionality of the family policy, which has a contradictory discourse, because while it contributes to women's economic autonomy, it also makes them even more responsible for the care and protection of their members, reinforcing women's impoverishment. Thus, women's participation in the programs is also contradictory, since the call for women's autonomy and empowerment advertised by these programs is related to the traditional roles of wife-mother-housewife and a certain romanticization of these functions, thereby camouflaging women's suffering in the face of these roles and reinforcing women's overload with domestic activities and care by exempting men from these occupations, This ends up preventing women from carrying out other paid work activities outside the home (or when they do, they feel more overburdened), contributing to female impoverishment. It is hoped that this study will enable new reflections and the construction of new knowledge beyond the academic field, and that the results obtained from this research will be given back to society through debate.